The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/10810730.2011.571335
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Communication about HIV Prevention in Kenya

Abstract: High HIV rates among cohabiting couples in many African countries have led to greater programmatic emphasis on spousal communication in HIV prevention. This study examines how demographic and socioeconomic characteristics of cohabiting adults influence their dyadic communication about HIV. A central focus of this research is on how the position of women relative to their male partners influences spousal communication about HIV prevention. The authors analyze gaps in spousal age and education and females' parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
6
1
Order By: Relevance
“…The overall finding is consistent with studies on marital subordination, interpersonal power, female monogamy, male multiple sexual partners, and HIV risk across SSA. 28,[57][58][59] This study finding also suggests an acceptance of social and cultural norms for masculinity, namely, ''acquiesced femininity'' (e.g., acceptance of men's dominance, control of economic resources, and multiple partners), regardless of a woman's empowerment status. 12,[60][61][62][63] Our findings differed from those of a multicountry DHS study in Gabon, Mozambique, Sierra Leone, and Zambia, a study in Cameroon, and DHS research in Eastern Africa reporting associations between women's empowerment and an increased likelihood of multiple sexual partnerships and HIV risk.…”
Section: Discussionsupporting
confidence: 57%
“…The overall finding is consistent with studies on marital subordination, interpersonal power, female monogamy, male multiple sexual partners, and HIV risk across SSA. 28,[57][58][59] This study finding also suggests an acceptance of social and cultural norms for masculinity, namely, ''acquiesced femininity'' (e.g., acceptance of men's dominance, control of economic resources, and multiple partners), regardless of a woman's empowerment status. 12,[60][61][62][63] Our findings differed from those of a multicountry DHS study in Gabon, Mozambique, Sierra Leone, and Zambia, a study in Cameroon, and DHS research in Eastern Africa reporting associations between women's empowerment and an increased likelihood of multiple sexual partnerships and HIV risk.…”
Section: Discussionsupporting
confidence: 57%
“…The varying social contexts within which women and their partners live, work and love create unique challenges for HIV prevention efforts ( Table 2). The number and type of partners, in large part influenced by structural factors and gender inequality [15], affect women's HIV risk perception and their ability to respond to that risk [16]. For example, the ability to use condoms consistently and correctly often varies by partner type [9,17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among an ethnically diverse sample of young couples in the United States, it was found that if the woman has sexual partners outside of their relationship this negatively affects SSC (Albritton et al, 2014). With regards to male partners, as opposed to facilitating SSC as it was recorded among Latino couples in this review (Ashburn et al, 2008), among cohabitating couples in Kenya, if the male had other sexual partners, the couple was less likely to have discussed HIV prevention (Chiao et al, 2011). …”
Section: Discussionmentioning
confidence: 96%
“…As in this review (Alvarez & Villarruel, 2015; Davila, 2002), past research with a sample of Latina women of mixed relationships status also found relationship power in general to be related to SSC (Davila, 1999). Similarly, among Kenyan women who are cohabitating with their male partners, participation in decision-making has been found to be positively associated with spousal communication about HIV prevention (Chiao, Mishra, & Ksobiech, 2011). Like the Latina women in studies included in this review (Davila, 2002), past research with African-American women who have stable partners has also found interpersonal violence to be related to various forms of SSC (Morales-Alemán et al, 2014).…”
Section: Discussionmentioning
confidence: 99%